STUDENTS’ PROFICIENCY IN TEACHING PHILIPPINE LITERATURE SUBJECT: A BASIS IN DEVELOPING POLYMEDIA MATERIALS - Nalud, Haipa; mangindra, anesa (International Journal of Arts, Sciences and Education, 2025)
This study examines students’ proficiency in teaching Filipino literature in the Philippines through the development of polymedia materials. Conducted at Sultan Kudarat State University, Palimbang Campus, during the second semester of the 2024-2025 academic year, it utilized a Research and Development (R&D) design. The research evaluated students’ skill levels, the effectiveness and validation of the developed polymedia materials, and their acceptance among teachers and students. Data were gathered through assessments, expert validation focusing on content and technical aspects, and an acceptability evaluation using mean and standard deviation. Findings indicated that students faced challenges in analyzing literary works and applying effective teaching strategies. However, the polymedia materials proved to be highly effective and were positively received by both teachers and students, highlighting their potential as supplementary teaching tools for Philippine literature. Based on these results, the study recommends the integration of polymedia to enhance students’ teaching proficiency while continuously refining its content and technical aspects for improved educational outcomes. Mga Susing Salita: akseptabilidad, balidasyon, kasanayan, pagtuturo ng Filipino, Panitikan ng Pilipinas, polymedia